The risk of developing cardiovascular disease in bipolar disorder. Biological factors and therapy - Sergey N. Mosolov; Elizaveta Yu. Fedorova (Терапевтический архив, 2022)
Background. Bipolar disorder (BD) is one of the most common mental disorders characterized by alternating episodes of mania/hypomania and depression, as well as the possibility of developing mixed conditions. Correct and timely diagnosis of BD is important due to the presence of a high suicidal risk and a high predisposition to the development of cardiovascular disease (CVD). The risk of CVD is higher in ВD than in other mental disorders.